Kebijakan Anggaran Responsif Gender di Kota PekalonganTahun 2016-2020 - Syifana Awan Ardhini; Turtiantoro - -; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2022)
Gender mainstreaming is still a fairly complex issue and often occurs among the people of Pekalongan City. Although the Pekalongan City government's commitment to gender mainstreaming has been stated in public policy documents, the government's commitment to realizing gender equality and justice in various development fields has so far not shown optimal results. The purpose of this study is to explain and describe the implementation of Gender Mainstreaming (PUG) in Pekalongan City in 2016-2020. Efforts to answer the problems and research objectives are carried out using gender responsive budget theory and budgeting policy theory. This research is descriptive qualitative. Data collection techniques using documentation and interviews. Data analysis used content analysis and interactive analysis techniques. The results of the study indicate that the allocation and amount of the gender responsive budget of Pekalongan City in 2016-2020 has not received an adequate allocation and continues to experience a decline resulting in the output and outcome of activities being not achieved. In addition, the amount of gender responsive budget from 2016-2020 is very minimal and continues to experience a significant decline. Constraints faced in the Gender Responsive budget policy in Pekalongan City include: 1) Policy constraints, namely the weak legal power for the implementation of gender mainstreaming in the budget and the weak commitment of the City Government in making gender responsive budget planning). 2) Structural constraints, namely the lack of capacity of the budget drafting team that is capable of gender analysis, the dominance of the structure of policy makers, the performance of the Office is still perceived as not being gender fair, and the absence of special cooperation in gender responsive budgeting. 3) Cultural constraints, including: (a) The patriarchal values are so thick in society. So the inequality of gender relations is very difficult to change. (b) The views of gender and gender responsive budgets according to stakeholders are still misguided.